"STATE OF CARBOHYDRATE-ENERGY, PIGMENT, PROTEIN METABOLISM IN THE LIVER IN CHRONIC TOXIC DAMAGE" - Mamasaidov Jamolidin Turg'inbayevich (Scholar Express Journals, 2022)
In recent years, the use of organophosphorus pesticides - Fozalon and Baton EU - has significantly expanded in agriculture. This circumstance puts forward as one of the priorities the elucidation of the mechanism of action and the development of specific prevention and treatment for chronic pesticide poisoning.
Keywords: phosphorylation; pyruvate substrates; oxaloacetic acid and liver succinate; protein